Smoking Among School Students – A Survey - C, Pratheebha; Ganapathy , Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
Adolescent tobacco smoking is a major health concern in India. Schools may be able to influence adolescent behaviour regarding smoking. Moreover, the prevalence of cigarette smoking varies between schools, and some of this variability may be explained by school factors. The World Health Organization (WHO) reported that mortality due to smoking-related diseases was higher than the combination of all infectious diseases worldwide. The aim of the study was to know the smoking habits among school students. Questions were prepared and administered to 120 participants through survey planet an online survey. The study population were school students of age group between 13 to18 years.26% of the respondents said they have the habit of smoking .64% of the smokers said they started smoking between 15-17 years, 31% said they started smoking between 17-18 years and 5% said they started smoking between 13-15 years .70% said they started smoking due to peer pressure,15% because of parental influence and 15% due to stress .54% were willing to stop the smoking habit .The school students are exposed to smoking due to parental influence ,peer pressure and stress. There is also willingness to stop smoking among students. More awareness programs should be conducted to educate the students on harmful effects of smoking.